PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMK SE KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - DefiSusanti DefiSusanti; Makhdalena Makhdalena; Azhar Azhar (Universitas Riau, 2017)
The purpose of study was to express the influence compensation and motivationwork concerning performance of the teacher SMK Se kecamatan Ujung Batu KabupatenRokan Hulu. Analysis data using doubled regression. This technique did to know influencecompensation variable (X1) and variable motivation teacher work (X2) concerning variableperformance teacher (Y). The total of subject research have been to fulfill requirement analyzewas 94 teacher of SMK Se Kecamatan Ujung Batu Kabupaten Rokan Hulu as the sample.Theresult of the test produce compensation and motivation work of simultaneously have influencesignificant with directive positive to performance teacher as big as 40,1 % and residue 59,9 %of influence by another factor such as behavior, attitude, and action collegue, subordinate andleadership, facility of performance and climate organization. Meanwhile, the influence partiallycompensation and motivation work to performance the teacher was the influence compensationto performance of the teacher. Compensation (X1) influential to performance the teacher (Y)in SMK Se Kecamatan Ujung Batu Kabupaten Rokan Hulu. The compensation give to contributeas big as 3,9% to performance of thr teacher. The influence motivation work to performanceof the teacher motivation work (X2) influential to performance of the teacher (Y) in SMK SeKecamatan Ujung Batu Kabupaten Rokan Hulu, the motivation work give contribute as big as30,9% to performance of theteacher.